Follow-up Rates After Teleretinal Screening for Diabetic Retinopathy: Assessing Patient Barriers to Care. (March 2023) - Patil, Sachi A.; Sanchez, Victor J.; Bank, Georgia; Nair, Archana A.; Pandit, Saagar; Schuman, Joel S.; Dedania, Vaidehi; Parikh, Ravi; Mehta, Nitish; Colby, Kathryn; Modi, Yasha S.
Purpose: To study patient follow-up after they engage in a teleretinal screening program and to understand potential barriers to care.Methods: This was a retrospective analysis and a prospective study of telephone-based patient interviews of outpatients screened for diabetic retinopathy (DR) through a teleretinal referral system.Results: Of 2761 patients screened through a teleretinal referral program, 123 (4.5%) had moderate nonproliferative DR (NPDR), 83 (3.0%) had severe NPDR, and 31 (1.1%) had proliferative DR. Of the 114 patients with severe NPDR or worse, 67 (58.8%) saw an ophthalmologist within 3 months of referral. Eighty percent of interviewed patients reported they were not aware of the need for follow-up eye appointments.Conclusions: Of patients with severe retinopathy or worse, 58.8% presented for in-person evaluation and treatment within 3 months of screening. Although this result was negatively affected by factors related to the COVID-19 pandemic, key elements of patient education and improved referral strategies to facilitate in-person treatment are essential to improving follow-up after patients engage in telescreening.